Effects of exercise preconditioning and HSP72 on diaphragm muscle function during mechanical ventilation. Issue 4 (10th April 2019) - Smuder, Ashley J.; Morton, Aaron B.; Hall, Stephanie E.; Wiggs, Michael P.; Ahn, Bumsoo; Wawrzyniak, Nicholas R.; Sollanek, Kurt J.; Min, Kisuk; Kwon, Oh Sung; Nelson, W. Bradley; Powers, Scott K.
Abstract: Background: Mechanical ventilation (MV) is a life‐saving measure for patients in respiratory failure. However, prolonged MV results in significant diaphragm atrophy and contractile dysfunction, a condition referred to as ventilator‐induced diaphragm dysfunction (VIDD). While there are currently no clinically approved countermeasures to prevent VIDD, increased expression of heat shock protein 72 (HSP72) has been demonstrated to attenuate inactivity‐induced muscle wasting. HSP72 elicits cytoprotection via inhibition of NF‐κB and FoxO transcriptional activity, which contribute to VIDD. In addition, exercise‐induced prevention of VIDD is characterized by an increase in the concentration of HSP72 in the diaphragm. Therefore, we tested the hypothesis that increased HSP72 expression is required for the exercise‐induced prevention of VIDD. We also determined whether increasing the abundance of HSP72 in the diaphragm, independent of exercise, is sufficient to prevent VIDD. Methods: Cause and effect was determined by inhibiting the endurance exercise‐induced increase in HSP72 in the diaphragm of exercise trained animals exposed to prolonged MV via administration of an antisense oligonucleotide targeting HSP72. Additional experiments were performed to determine if increasing HSP72 in the diaphragm via genetic (rAAV‐HSP72) or pharmacological (BGP‐15) overexpression is sufficient to prevent VIDD. Results: Our results demonstrate that the exercise‐induced increase in HSP72 protein abundance is required for the protective effects of exercise against VIDD. Moreover, both rAAV‐HSP72 and BGP‐15‐induced overexpression of HSP72 were sufficient to prevent VIDD. In addition, modification of HSP72 in the diaphragm is inversely related to the expression of NF‐κB and FoxO target genes. Conclusions: HSP72 overexpression in the diaphragm is an effective intervention to prevent MV‐induced oxidative stress and the transcriptional activity of NF‐κB and FoxO. Therefore, overexpression of HSP72 in the diaphragm is a potential therapeutic target to protect against VIDD.